Sejarah Konsep Matematika dalam Peradaban Islam dan Implementasinya dalam Kehidupan - Ruhiat, Devina Juniar; Puspitarani, Mayra; Salma, Syakurah; Fajrussalam, Hisny (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Knowledges in Islam has progressed from the past until now. In Islam, knowledges has a solid foundation through the Qur'an and Sunnah, sourced from the physical and metaphysical realms. Knowledge also includes not only worldly but also related to the problems of the hereafter. The purpose of this study is to explain the disciplines of mathematics in Islam and how mathematics is applied in Islam. This research method is a literature study based on theory or journal studies. The results of the research here can be concluded that Mathematics has existed and has been useful since the Hijri era. One of them is useful in calculating for inheritance, calculating zakat fitrah, and other things that are still useful from the past until now.